2001
DOI: 10.1021/jp0034271
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of Metal−Arene Compounds:  Mono(benzene)chromium, Bis(benzene)chromium and Their Cations

Abstract: To investigate the elementary events of the decomposition of transition metal complexes, a density functional study of the systems Cr(C 6 H 6 ) 2 and Cr(C 6 H 6 ) as well as their corresponding cations, has been carried out. The results give a low bond energy (0.36 eV) for the neutral Cr(C 6 H 6 ) compound while the binding energy of the cation Cr(C 6 H 6 ) + is much higher (1.84 eV), in good agreement with previous theoretical and experimental studies. Concerning the dissociation of Cr(C 6 H 6 ) 2 , the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 66 publications
4
36
0
Order By: Relevance
“…The average metal-ligand bond energy of bis(arene)chromium (about 160 kJ•mol −1 ) is significantly lower than that of C-C bonds (about 500 kJ•mol −1 ) and C-H bonds (about 450 kJ•mol −1 ) [52,53]. For bis(arene)chromium (BBC and BEBC), the dissociation energy of the metal-ligand bonds determines the efficiency of the process [51].…”
Section: Kinetic Pathways: Study Of the Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average metal-ligand bond energy of bis(arene)chromium (about 160 kJ•mol −1 ) is significantly lower than that of C-C bonds (about 500 kJ•mol −1 ) and C-H bonds (about 450 kJ•mol −1 ) [52,53]. For bis(arene)chromium (BBC and BEBC), the dissociation energy of the metal-ligand bonds determines the efficiency of the process [51].…”
Section: Kinetic Pathways: Study Of the Reactionsmentioning
confidence: 99%
“…About gas-surface reactions, the non-dissociative adsorption of MBC was not retained because the low bond energy of Cr-C 6 H 6 (35 kJ•mol −1 ) [53] makes this reaction unlikely with regard to dissociative adsorption of MBC on a Cr site (Reaction (2)). Also, the non-dissociative adsorption of BBC on Cr sites is an unlikely reaction since the surface species that would be produced would certainly be less stable than BBC itself, which is supposed to be readily decomposed in the gas phase according to reaction 1.…”
Section: No Reactionsmentioning
confidence: 99%
“…The more stable clusters correspond to sizes containing enough electrons to fill the electronic shells. 2 Such a model has been used to understand the stability and electronic properties of numerous metal clusters and was recently 3,4 used to demonstrate the superhalogen behavior of Al 13 − . Another class of stable clusters are the fullerenes, 5 e.g., C 60 and bigger cages.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many experimental [5][6][7][8][9][10][11][12][13][14][15] and theoretical [16][17][18][19][20][21][22][23][24][25][26][27][28][29] investigations on the interaction of metal clusters with benzene in gas phase were extensively reported. Kaya group [5][6][7] systematically studied the properties of 3d transition metal-benzene complexes M m (benzene) n (M = Sc, Ti, V, Cr, Mn, Fe, Co, Ni) in the gas phase, including their structures, photodissociation processes, bonding energies and ionization energies.…”
Section: Introductionmentioning
confidence: 99%
“…Kaya group [5][6][7] systematically studied the properties of 3d transition metal-benzene complexes M m (benzene) n (M = Sc, Ti, V, Cr, Mn, Fe, Co, Ni) in the gas phase, including their structures, photodissociation processes, bonding energies and ionization energies. But the reported experimental [12][13][14][15] and theoretical [19,[22][23][24][25][26][27][28][29] studies are mainly on the transition metal-benzene cationic and neutral complexes. However, the experimental and theoretical studies of metal-benzene anion complexes are rarely reported.…”
Section: Introductionmentioning
confidence: 99%